Analyzing the Relationship Between Electricity Access and Renewable Energy on Indonesia's Economic Growth from 1985 to 2022 - Adi Rahmansyah; Ida Budiarty; Dedy Yuliawan (Nomico, 2025)
This study aims to analyze the relationship between access to electricity and renewable energy on economic growth in Indonesia, using a quantitative descriptive approach. Time series data from 1985 to 2022 was sourced from World Development Indicators and Our World in Data. The Vector Error Correction Model (VECM) was used in this study after the existence of cointegration between variables was proven. The estimation results found that all independent variables have a positive and statistically significant relationship with economic growth, with the surprising finding that, in the long term, the impact of renewable energy (1.14%) is relatively greater than the impact of electricity access (0.29%) on economic growth. Going forward, the contribution of renewable energy to economic growth is predicted to increase in line with the SDG targets. Indonesia's energy sector reforms have had a significant impact in reducing the effects of climate change and freeing the country from fossil fuels.